PENGENDALI LOGIKA FUZZY PADA MEKANISME GERAKAN LURUS PRESISI - Ilham Budi Santoso; Zainal Abidin (Mesin, 1998)
This paper discusses the implementation of a fuzzy logic controller on a precision straight-line motion mechanism. The precision straight-line motion mechanism, which is studied in this research, is a mechanism that was built to study methods of precision positioning. For this mechanism, a conventional PID (Proportional, Integral, and Derivative) controller will not beable to produce good performances because of non-linearity behavior of this mechanism. This paper shows that a fuzzy logic controller based on knowledge of a human (an operator) can solve this nonlinearity problem.